Legal Protection for Children Victims of Neglect by Parents with Mental Disorders within Indonesia’s Legislative Framework - Citra Agustine Putri Rumpaidus (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
The issue of child neglect by parents with mental disorders raises complex legal and social challenges, as both the child and the mentally ill parent are vulnerable groups requiring legal protection and State responsibility to ensure their rights. Mental illness often impairs parental capacity to provide adequate care, placing the child in a highly vulnerable and precarious situation. From a criminal law perspective, such mental conditions may serve as a ground for excuse under the Indonesian Penal Code, potentially eliminating criminal responsibility. This raises the question of who is accountable for ensuring the child's protection. This normative legal research aims to analyze the available forms of legal protection for children in such circumstances under Indonesian law, particularly Law No. 23 of 2002 on Child Protection as amended by Law No. 35 of 2014, and to examine State responsibility through the lens of Child Rights Theory and the Best Interests of the Child principle. The study finds that while Indonesia's legal framework is relatively comprehensive, highlighted by Government Regulation No. 44 of 2017 on the Implementation of Child Care and Government Regulation No. 78 of 2021 on Special Protection for Children, implementation remains hindered by significant challenges, including weak institutional coordination, limited resources, and an insufficiently child-centered approach. The State thus has a positive obligation to take concrete preventive and curative measures to ensure children's rights protection, including providing appropriate alternative care and access to psychosocial recovery services.